Chemical and antioxidant characteristics on rice crackers fortified with seaweed Eucheuma cottoni and dayak onion - Christine Dyta Nugraeni; Dena Pramita Dewi; Tuty Alawiyah; Gazali Salim; Tri Paus Hasiholan Hutapea (Arwana: Jurnal Ilmiah Program Studi Perairan, 2023)
This study aims to observe the addition of seaweed and Dayak onions to rice crackers on the nutritional content and antioxidant activity. This study has been carried out at the Nutrition Laboratory, University of Borneo Tarakan. The seaweed used is Eucheuma cottoni. Making crackers consists of several steps, namely material preparation, dough making, molding, and drying. The results given information that the addition of seaweed and Dayak onions had an effect on the nutritional content and antioxidant activity. Puli crackers fortified with seaweed and Dayak onions contain 8.04% protein, 1.07% fat, 1.77% water, 5.96% ash, and 83.16% carbohydrates. The antibiotic activity of seaweed and Dayak onion fortified Puli crackers using the DPPH method was greater than that of commercial Puli crackers, which was 4.07%.